Therapeutic potential of Ganoderma lucidum/ Reishi mushroom - Rehman, Aroosa; Siddique, Bushra; Nadeem, Amna; Mateen, Abdul (Journal of the Pakistan Medical Association, 2025)
Ganoderma lucidum, commonly known as Reishi mushroom, has a history of use in traditional Chinese, Japanese, and Korean medicine. It has the ability to support treatments for diseases such as diabetes, neurodegenerative disorders, atherosclerosis, and inflammation. Polysaccharides extracted from G. lucidum exhibit antioxidant, immunomodulatory, anticancer, and antibacterial properties, establishing it as a versatile therapeutic agent.. Highlighting its role in cancer therapy, according to Ünlü A et al., G. lucidum extracts exhibit anti-proliferative effects, including apoptosis induction, cell cycle arrest in tumour cells, and enhancement of natural killer (NK) cell cytotoxicity against cancer cells. The mushroom also inhibits angiogenic factors, suggesting a potential chemotherapeutic application.1 In China, G. lucidum has been clinically utilized since 1973. According to a study by Chang ST et al., after 1990s Ganoderma products gained popularity in regions such as Europe, Malaysia, North America, and Singapore.2 As per study by Bijalwan A et al., India has become a major market for herbal products, including Ganoderma. Increased awareness and accessibility through online platforms and multi-level marketing have contributed to this growth. The Indian Ganoderma-based nutraceutical market was valued at approximately USD 20 million in 2012.3 In Pakistan, G. lucidum remains underexplored despite its therapeutic potential. Sharif S et al. reported that G. lucidum is cultivated and isolated in Jinnah Garden, Faisalabad.4 Ganoderma lucidum has significant potential to revolutionize health treatments in Pakistan. Its application in treating cancer and other ailments can offer a novel, cost-effective solution to reduce morbidity and mortality rates. Further investment in research and development of G. lucidum-based therapies is essential to realise its full potential.